Analysis of The Simpang Lolo Educational Forest Tourism Potential as an Alternative Tourism Development In the Gunung Tuleh Sub-District of West Pasaman District (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The prospect of the tourism industry is very promising in increasing Gross Domestic Product (GDP), which is 4.1% directly and 9% indirectly. In order for GDP to continue to increase, one of the efforts is to improve the tourism sector. In this study, tourism analysis was carried out in the Simpang Lolo educational forest area, West Pasaman Regency with the aim that tourism in this area can be built and developed so that it can become an attractive tourist icon and can help improve community welfare. This research uses a quantitative SWOT method that emphasizes the External Factor Analysis Summary (E FAS) matrix which includes opportunities and threats with a resulting score of 2.83 and Internal Factor Analysis Summary (IFAS) which includes strengths and weaknesses with a resulting score of 2.5. This shows that the Simpang Lolo Education Forest has a strong internal capacity and can make innovations and improvements to further enhance the internal resources that are its strengths. In its external capacity, Simpang Lolo Educational Forest can respond and take advantage of opportunities and threats in the tourism industry, especially in educational forest tourism.